Distinct conformers of transmissible misfolded SOD1 distinguish human SOD1-FALS from other forms of familial and sporadic ALS - Ayers, Jacob I.; Diamond, Jeffrey; Sari, Adriana; Fromholt, Susan; Galaleldeen, Ahmad; Ostrow, Lyle W.; Glass, Jonathan D.; Hart, P. John; Borchelt, David R. (Acta neuropathologica, 2016)
Evidence of misfolded wild-type superoxide dismutase 1 (SOD1) has been detected in spinal cords of sporadic ALS (sALS) patients, suggesting an etiological relationship to SOD1-associated familial ALS (fALS). Given that there are currently a number of promising therapies under development that target SOD1, it is of critical importance to better understand the role of misfolded SOD1 in sALS. We previously demonstrated the permissiveness of the G85R-SOD1:YFP mouse model for MND induction following injection with tissue homogenates from paralyzed transgenic mice expressing SOD1 mutations. This prompted us to examine whether WT SOD1 can self-propagate misfolding of the G85R-SOD1:YFP protein akin to what has been observed with mutant SOD1. Using the G85R-SOD1:YFP mice, we demonstrate that misfolded conformers of recombinant WT SOD1, produced in vitro, induce MND with a distinct inclusion pathology. Furthermore, the distinct pathology remains upon successive passages in the G85R-SOD1:YFP mice, strongly supporting the notion for conformation-dependent templated propagation and SOD1 strains. To determine the presence of a similar misfolded WT SOD1 conformer in sALS tissue, we screened homogenates from patients diagnosed with sALS, fALS, and non-ALS disease in an organotypic spinal cord slice culture assay. Slice cultures from G85R-SOD1:YFP mice exposed to spinal homogenates from patients diagnosed with ALS caused by the A4V mutation in SOD1 developed robust inclusion pathology, whereas spinal homogenates from more than 30 sALS cases and various controls failed. These findings suggest that mutant SOD1 has prion-like attributes that do not extend to SOD1 in sALS tissues.